2020
DOI: 10.52168/bjf.2020.32.08
|View full text |Cite
|
Sign up to set email alerts
|

Water quality and fish diversity in Korotoa River of Bogura, Bangladesh

Abstract: The study was conducted to explore the physicochemical parameters of water, fish diversity andfisheries resources of Korotoa River at Bogura city of Bangladesh during July 2015 to February 2016. Thewater samples were collected from five sampling stations in the Korotoa River during wet and dry seasons.The results of the study showed that temperature, EC, TDS, DO, BOD, alkalinity, acidity and total hardnessof the Karotoa River water were 25.86ºC, 297.41 ?S/cm, 98.86 mg/L, 2.17 mg/L, 2.64 mg/L, 122.05mg/L, 3.28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…The total alkalinity decreased from 135.14 ± 3.57 mg/L in June to 77.97 ± 0.82 mg/L in July. The mean alkalinity of the Korotoa River water (122.05 mg/L) was similar to the current study [ 47 ]. TDS levels in the haor ranged from a peak of 140.45 ± 1.30 mg/L in May to a low of 83.77 ± 1.79 mg/L in July.…”
Section: Discussionsupporting
confidence: 88%
“…The total alkalinity decreased from 135.14 ± 3.57 mg/L in June to 77.97 ± 0.82 mg/L in July. The mean alkalinity of the Korotoa River water (122.05 mg/L) was similar to the current study [ 47 ]. TDS levels in the haor ranged from a peak of 140.45 ± 1.30 mg/L in May to a low of 83.77 ± 1.79 mg/L in July.…”
Section: Discussionsupporting
confidence: 88%
“…Khan et al (1996) also revealed a higher level of PO 4 -P in dry season compared to rainy season in their study location. Total alkalinity was 126.89±7.47 mg/L in pre-monsoon to 103.38±4.44 mg/L during monsoon season which is more or less similar to the findings of Ahatun et al (2020) in Korotoa River (122.05 mg/L). The peak TDS content of the haor was 135.73±5.50 mg/L throughout pre-monsoon mg/L, and the lowermost was 100.97±5.16 mg/L in monsoon season.…”
Section: Discussionsupporting
confidence: 80%
“…People involved in all these works, earning money for their daily needs and they can maintain their family expense. There are a great impact in the local community and socio economic condition [22]. All of those activity is directly related to fish production as well as river water quality.…”
Section: Discussionmentioning
confidence: 99%